Feminist Theory, Women's Writing - Finke, Laurie A. (Cornell University Press, 2018)
In this rewarding book, Laurie A. Finke challenges assumptions about gender, the self, and the text which underlie fundamental constructs of contemporary feminist theory. She maintains that some of the key concepts structuring feminist literary criticism need to be reexamined within both their historical context and the larger framework of current theory concerning language, representation, subjectivity, and value.